2018
DOI: 10.1016/j.bbmt.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Double-Expressor Lymphoma Is Associated with Poor Outcomes after Allogeneic Hematopoietic Cell Transplantation

Abstract: Double-expressor lymphoma (DEL) is a diffuse large B cell lymphoma that exhibits co-expression of MYC and BCL2 proteins by immunohistochemistry. Patients with double-expressor lymphoma have a poor prognosis after standard chemoimmunotherapy or after high-dose chemotherapy with autologous transplantation, but the prognostic impact of DEL after allogeneic hematopoietic cell transplantation has not been well characterized. We retrospectively analyzed 60 consecutive patients with de novo diffuse large B cell lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 32 publications
(41 reference statements)
0
14
0
Order By: Relevance
“…This result is consistent with the fact that DE-DLBCL is more aggressive than the non-DEL subtype. 3,6,[10][11][12][13][14][15][16] Conversely, the OS rate was significantly lower in the DEL group than in the non-DEL group. We found that 94% of R/R DE-DLBCL patients did not respond to salvage chemotherapy and died from progressive disease (PD).…”
Section: Resultsmentioning
confidence: 93%
“…This result is consistent with the fact that DE-DLBCL is more aggressive than the non-DEL subtype. 3,6,[10][11][12][13][14][15][16] Conversely, the OS rate was significantly lower in the DEL group than in the non-DEL group. We found that 94% of R/R DE-DLBCL patients did not respond to salvage chemotherapy and died from progressive disease (PD).…”
Section: Resultsmentioning
confidence: 93%
“…[23][24][25] T A B L E 3 Summary of published studies of ASCT for non-Hodgkin's lymphoma Multiple retrospective studies have shown that patients with coexpression of MYC and BCL-2 proteins in immunohistochemistry have poor outcomes, with long-term PFS ranging from 3% to 49.4%. [25][26][27] Despite having an international prognostic index (IPI)…”
Section: Discussionmentioning
confidence: 99%
“…Although FISH using a break‐apart probe for MYC ‐R was adopted in many studies, this method cannot detect the translocation partner of the MYC gene. Recently, several investigators reported that the prognosis of patients with MYC ‐R who received immunochemotherapy was affected by the translocation partner of MYC 34‐37 . Patients with MYC ‐ IG rearrangements had inferior survival to those with MYC ‐non‐ IG 36 .…”
Section: Discussionmentioning
confidence: 99%